Nilai Religius Dalam Novel Tuhan, Aku Kembali Karya Haidar Musyafa - Sri Mulyani Rusli (Fakultas Sastra Universitas Ekasakti, 2020)
This research motivated by the existence of Islamic religious values in novel God's I Back by Haidar Musyafa. The value of Islamic religion in terms of the value of aqidah, sharia values and moral values by Haidar Musyafa. The purpose of this research to describe the values of aqidah, shari'a and morals in novel by Haidar Musyafa. The type of research is qualitative research. The method used in this research descriptive method of analysis. The data of this research are religious data about the value of creed, morals and characters contained in the novel by Haidar Musyafa. Based on the analysis of research data can be concluded that the value of aqid contained in the novel Haidar Musyafa's, namely (a) faith to Allah SWT (belief in Allah) seen on the character Umi stating that God's promise that His pleasure depends on the pleasure of both parents. (b) faith in the books of Allah swt reflected on the character of Jefry who likes to read the holy verses of the Qur'an in the race. Sharia value is depicted on Apih figures who ordered their children to perform congregational prayers and chips in order not to leave the prayer. Furthermore, the moral values are (a) morals towards Allah (khalik) is depicted on the character of Jefry who initially have habbit not good then repent to be good people. (b) morals towards humans depicted on the character Jefry who like do something not good, being rude and not obeying the words of parents.